AB0084 BehÇet's disease and budd-chiari syndrome: two cases with diverse progresses. (1st June 2001) - Aksu, K; Keser, G; Inal, V; Oksel, F; Kocanaogullari, H; Tokat, Y; Batur, Y; Gümüsdis, G; Doganavsargil, E
Abstract : Background: Behçet's disease (BD) is a systemic vasculitis of unknown aetiology that can lead to thrombosis of both veins and arteries of various sizes. Thrombosis of hepatic veins, known as Budd-Chiari syndrome (BCS) may be seen in BD, with variable clinical courses as described in 2 patients: Case 1: Thirty-four year-old male patient had oral and genital ulcers and erythema nodosum for 2 years. Within two weeks after presentation, thrombosis of hepatic veins and vena cava inferior was found, while evaluating the patient for abdominal pain and liver function test abnormalities. The patient well responded to the treatment consisting high dose prednisolone, pulse cyclophosphamide and anticoagulant drugs with recanalisation of the veins. At the end of two years, the patient has still been in clinical remission. Case 2: A twenty year-old male patient had oral and genital ulcerations for 4 years and had an episode of uveitis 4 years ago. He was referred to our clinic because of abdominal distension and oedema of lower extremities lasting for 4 months. The laboratory analyses disclosed ascites, grade III varicosity of oesophagus and thrombosis of hepatic veins and vena cava inferior. Mesoatrial shunt operation was performed when the initial treatment with pulse cyclophosphamide and high dose prednisolone failed. Obliteration of the shunt was observed by doppler ultrasonography, performed one week after the operation. He did not respond to the supportive therapy after the shunt operation and was lost with gastrointestinal bleeding. Objectives: Methods: Results: Conclusion: These two male Behçet's patients with BCS are examples of diverse prognoses, probably depending upon how early the diagnosis is made, and how efficient the treatment is. BCS in BD, may have a better prognosis if the diagnosis is made earlier and the treatment started sooner in the course of the disease.